2018
DOI: 10.1186/s11671-018-2539-9
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Efficiency-Droop-Free AlGaN-Based Ultraviolet Light-Emitting Diodes with a Specifically Designed Superlattice p-Type Electron Blocking Layer for High Mg Doping Efficiency

Abstract: This work reports a nearly efficiency-droop-free AlGaN-based deep ultraviolet light-emitting diode (DUV LED) emitting in the peak wavelength of 270 nm. The DUV LED utilizes a specifically designed superlattice p-type electron blocking layer (p-EBL). The superlattice p-EBL enables a high hole concentration in the p-EBL which correspondingly increases the hole injection efficiency into the multiple quantum wells (MQWs). The enhanced hole concentration within the MQW region can more efficiently recombine with ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 28 publications
(35 reference statements)
0
49
0
Order By: Relevance
“…AlGaN-based deep ultraviolet light-emitting diodes (DUV LEDs) can be widely used in the fields of solid-state lighting, medicine, biochemistry, and so on. Therefore, more and more efforts have been devoted to improve the crystal quality of the materials [ 1 4 ], the p-type doping techniques, and the optimization of the device structures [ 5 9 ]. Miyake et al demonstrated that the AlN crystal quality can be improved significantly by high-temperature annealing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…AlGaN-based deep ultraviolet light-emitting diodes (DUV LEDs) can be widely used in the fields of solid-state lighting, medicine, biochemistry, and so on. Therefore, more and more efforts have been devoted to improve the crystal quality of the materials [ 1 4 ], the p-type doping techniques, and the optimization of the device structures [ 5 9 ]. Miyake et al demonstrated that the AlN crystal quality can be improved significantly by high-temperature annealing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As has been proposed by other groups, the electron leakage for DUV LEDs can be reduced after enhancing the hole injection [19][20][21]. However, the proposals may affect the crystalline condition for the subsequently grown p-type layer.…”
Section: Resultsmentioning
confidence: 87%
“…As reported, the efficiency droop decreases from 54% to 34% when an n-AlN/AlGaN EBL is utilized [19]. The Al 0.45 Ga 0.55 N/Al 0.60 Ga 0.40 N superlattice p-EBL also helps to reduce the efficiency droop from 24% to 4% [20]. The multiple quantum wells (MQWs) with Mg doped quantum barriers can achieve the alleviated efficiency droop [21].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, because ionized impurities in the materials have a scattering effect on carriers and thus reduce carrier mobility, the undoped GaN layer in the multi-layer stacking structure allows for higher electron mobility than the traditional n-AlGaN layer, which will enhance the current spreading capability of the devices. To further explore the internal mechanisms of a multi-layer stacked n-AlGaN/u-GaN structure that promotes uniform current spreading, the partial conduction band energy and electron concentration in the AlGaN/GaN structure, and the hole concentration in the first quantum well of both samples, were calculated by the advanced physical model of semiconductor devices (APSYS) [34], which includes the tunneling and heterojunction models. The operating temperature, the Shockley-Read-Hall recombination lifetime, and the screening factor were set to 300 K, 100 ns, and 20%, respectively.…”
Section: Methodsmentioning
confidence: 99%